Control of former political prisoners and deportees in KGB documents - Burinskaitė, Kristina (Genocidas ir rezistencija, 2006)
Until 1990, the struggle against the Lithuanian anti–Soviet underground, dissidents defending human rights and freedoms, and Lithuanian diaspora organisations as well as their campaigns for the liberation of Lithuania were one of the most prominent operational areas of LSSR’s KGB subject to supervision by the KGB 5th division from 1967. The main function of the latter was ideological counterintelligence, i.e., fight against external and internal forces hostile to the Soviet regime. These forces included persons returning from exile and imprisonment. The Soviet authorities kept its firm grip on the Lithuanian intelligentsia – the former political and cultural elite of the Republic of Lithuania. The terror of 1941 and 1944–1953 was directed at prominent Lithuanian politicians, public and cultural figures. They were not only prevented from returning to their home countries, but also subjected to various obstacles upon their return. KGB agents closely monitored the lifestyle and behaviour of deportees and prisoners upon their return. The label of ‘enemies of the people’ followed them and their children even after their return to Lithuania. They were prevented from integrating into society, reclaiming their former social status they had enjoyed in independent Lithuania, and finding a job in line with their educational background. They were seen as a potential anti–Soviet force to be supervised, controlled, and punished.
Keywords: KGB; KGB methods; political prisoners; deportees